Hunting for Hemingway [large type] - Madsen, Diane Gilbert (Madsen, Diane Gilbert. DD McGil literati mystery., 2010)
Although insurance investigator DD McGil has always had her choice of lovers, she's been spectacularly unlucky in love. Now one of her former flames, Hemingway expert David Barnes, claims to have recovered the legendary stories and poems that Hemingway's first wife lost on a train. Barnes plans to auction them for millions, but controversy rages. Are they real or forged? Found? Or stolen? DD's quest to find out puts her on the trail of a killer. The hunter quickly becomes the hunted when someone tries to stop her - dead .